HS‐AFM and SERS Analysis of Murine Norovirus Infection: Involvement of the Lipid Rafts. Issue 1 (7th November 2016) - Aybeke, Ece N.; Belliot, Gaël; Lemaire‐Ewing, Stéphanie; Estienney, Marie; Lacroute, Yvon; Pothier, Pierre; Bourillot, Eric; Lesniewska, Eric
Abstract : Studies on human norovirus are severely hampered by the absence of a cell culture system until the discovery of murine norovirus (MNV). The cell membrane domains called lipid rafts have been defined as a port of entry for viruses. This study is conducted to investigate murine norovirus binding on the mouse leukemic monocyte macrophage cell line. Lipid raft related structures are extracted from cells by detergent treatment resulting detergent‐resistant membrane (DRMs) domains. The real‐time polymerase chain reaction technique is performed to detect the viral genome, thereby the MNV binding on the DRMs. The interactions between MNV and DRMs are investigated by high‐speed atomic force microscopy (HS‐AFM) combined with surface‐enhanced Raman spectroscopy (SERS). The inoculation of the virus onto cells results in the aggregations of detergent‐resistant membrane domains significantly. The characteristic Raman band of MNV is found in inoculated samples. To be sure that these results are originated from specific interactions between DRM and MNV, methyl‐β‐cyclo‐dextrin (MβCD) is applied to disrupt lipid rafts. The MNV binding on DRMs is precluded by the MβCD treatment. The cholesterols chains are defined as a key factor in the interactions between norovirus and DRMs. The authors conclude that the MNV binding involves the presence of DRMs and cholesterol dependent. Abstract : Murine norovirus (MNV) infection on membrane of mouse leukaemic monocyte macrophage cells (RAW) are investigated using a new high‐speed atomic force microscopy (HS‐AFM) and surface enhanced Raman spectroscopy (SERS) platform. Using this advanced platform, the study suggests that norovirus binding is cholesterol‐dependent and closely associated with detergent resistant membranes (DRMs).